The novel long noncoding RNA Lnc19959.2 modulates triglyceride metabolism-associated genes through the interaction with Purb and hnRNPA2B1 - Jing Wang; Dao Xiang; Shuai Mei; Yuanchao Jin; Dating Sun; Chen Chen; Dong Hu; Shiyang Li; Huihui Li; Yan Wang; Dao Wen Wang; Hu Ding (Elsevier, 2020)
Objective: Long noncoding RNAs (lncRNAs) are currently considered to have a vital and wide range of biological functions, but the molecular mechanism underlying triglycerides metabolism remains poorly understood. This study aims to identify novel lncRNAs differentially expressed in rat livers with hypertriglyceridemia and elucidated the function role in TG metabolism. Methods: Differentially expressions of lncRNAs in rat livers with hypertriglyceridemia were identified by transcriptome sequencing and validated by real-time PCR. The role of lnc19959.2 in triglyceride metabolism was assessed both in vitro and in vivo. RNA pulldown and RIP assays were conducted to evaluate the interactions between lnc19959.2 and its target proteins. ChIP and Dual report assays were performed to detect the interactions between transcription factors and promoters of its target genes. Results: We identified a novel lncRNA, and lnc19959.2 was upregulated in rat livers with hypertriglyceridemia. The knockdown of lnc19959.2 has profound TG lowering effects in vitro and in vivo. Subsequently, the genome-wide analysis identified that the knockdown of lnc19959.2 caused the deregulation of many genes during TG homeostasis. Further mechanism studies revealed that lnc19959.2 upregulated ApoA4 expression via ubiquitinated transcription inhibitor factor Purb, while it specifically interacted with hnRNPA2B1 to downregulate the expression of Cpt1a, Tm7sf2, and Gpam, respectively. In the upstream pathway, palmitate acid upregulated CCAAT/Enhancer-Binding Protein Beta (Cebpb) and facilitated its binding to the promoter of lnc19959.2, which resulted in significant promotion of lnc19959.2 transcriptional activity. Conclusions: Our findings provide novel insights into a new layer regulatory complexity of an lncRNA modulating triglyceride homeostasis by a novel lncRNA lnc19959.2.